Surgical Management of Thoracolumbar Myelopathies in Pug Dogs with Concurrent Articular Facet Dysplasia - Tauro, Anna; Rose, Jeremy; Rusbridge, Clare; Driver, Colin J. (VCOT Open, 2019)
Objectives The aim of this article is to present the outcome of vertebral stabilization using pins and polymethylmethacrylate in isolation or with concurrent spinal cord decompression for thoracolumbar myelopathies in Pug dogs with associated caudal articular process dysplasia.Materials and Methods Retrospective case review of 14 Pug dogs with thoracolumbar myelopathy and concurrent caudal articular process dysplasia identified with magnetic resonance imaging and computed tomography. Pug dogs were graded based on the Texas Spinal Cord Injury Scale and clinical follow-up was performed immediately after surgery, at the discharge and at during the postoperative period (median 5 months). Postoperative computed tomography was performed immediately post-surgical intervention in all cases and a variable postoperative time (6 weeks or 6 months). Follow-up with telephone interview with owners was performed at a median time of 12 months postoperatively.Results Median age of presentation was 8.5 years. In 10/14 cases, neurological improvement was observed, while urinary/faecal incontinence resolved in only two of seven affected cases. Other congenital vertebral malformations were identified in 9/14 cases.Clinical Significance In our population of Pug dogs with thoracolumbar myelopathy and concurrent caudal articular process dysplasia, vertebral stabilization in isolation or with concurrent spinal cord decompression appeared to result in a favourable clinical outcome in the majority of patients. This technique may be favourable for myelopathies with a reportedly poor surgical outcome in this breed.
Keywords: thoracolumbar myelopathy; vertebral instability; arachnoid diverticulum; pia-arachnoid fibrosis; intervertebral disc protrusion